2018
DOI: 10.1186/s13065-018-0449-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyetherimide membrane from non-toxic solvents for the separation of hydrogen from methane

Abstract: Polymeric membranes are usually prepared from solvents like n-methylpyrrolidone (NMP) because of the strong dissolving power and high boiling point. Yet, the solvent is costly, toxic and has environmental issues. In this work, nontoxic solvents such as methyl l-lactate, ethyl lactate, propylene carbonate, tributyl o-acetylcitrate, tributyl citrate, triethyl phosphate, and γ-butyrolactone (GBL) were introduced during membrane preparation. It was found that all the solvents were unable to dissolve polyetherimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Before coating the sample, it is advised to insert the sample in liquid nitrogen for a few minutes then cut it by a sharp blade. This will result in a better image and eliminates surface bend [15].…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Before coating the sample, it is advised to insert the sample in liquid nitrogen for a few minutes then cut it by a sharp blade. This will result in a better image and eliminates surface bend [15].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Usually, the angle starts from 10 to 80 and each compound has a defined set of peaks. For example, polyetherimide is known to have sharp peaks at 21.4 and 23.8 (2θ) [15]. If additional peaks were detected for a pure polyetherimide membrane, this may indicate impurities or membrane degradation.…”
Section: Data Interpretationmentioning
confidence: 99%
“…In addition, the performance of the dip-coated carbon membranes presented in this work was better than the polymeric membranes prepared in our previous study in terms of selectivity and permeability using the same evaluation unit. 17 In summary, the method described in this study avoids the lengthy process and the toxic solvents involved in the conventional precursors and preparation methods. Therefore, the work presented in this study is a step forward in the preparation of carbon membranes, and it should be bene-cial in the future development of carbon membranes.…”
Section: Resultsmentioning
confidence: 98%
“…Another variable, i.e., feed pressure, was also tested, as noted from the results that indicated that there was a trade-off between the uxes and selectivity. 17 As the feed pressure increased, the selectivity decreased and the uxes increased. Fig.…”
Section: Experimental Workmentioning
confidence: 99%
“…Prepared using a green process, the resulting membranes were defect-free ultrafiltration membranes. Alqaheem et al [ 72 ] investigated methyl lactate to fabricate polyetherimide (PEI) membranes on the basis that the Hansen solubility parameter indicated methyl lactate had the potential to dissolve PEI, though the experiments subsequently failed to support this notion. The membranes prepared with methyl lactate have exhibited several defects and quality issues, such as inhomogeneity, micro-voids appearing on the surface and varying water permeability [ 71 ].…”
Section: Membrane Fabricationmentioning
confidence: 99%